“In the thick darkness of this plague”: the furious christian God and the punitive aspect of epidemics in fictional literature: “In the thick darkness of this plague”: the furious christian God and the punitive aspect of epidemics in fictional literature (Revista de História da UEG (REVHIST), 2025)
This article is conducted by the problem of the correlation between History and literature, focusing on the analysis of a selection of fictional literary productions in regards, specifically, to the presence of the concept of the Christian God’s wrath as the primary cause of plague epidemics – to which a disciplinary attribute is given. In this sense, here it is taken into account the dynamics of transposition – to the literary sphere – of an ecclesiastical reference based on the thesis of the action of an angry God who punishes humanity based on its earthly behavior. As a result, the nuances of this aforementioned aspect are investigated in works produced at different times by authors coming from different origins, such as The Decameron, by the Italian Giovanni Boccaccio; A Journal of the Plague Year, by the British Daniel Defoe; and The Plague, by the French-Algerian Albert Camus. This research emphasizes, however, that it is very important for the historian to be cautious in the process of historical reading of fictional texts – so that their essential literary nature is conserved.Keywords: Divine wrath. Christian God. Epidemics. History and literature. Church.
Keywords: Divine wrath; Christian God; Epidemics; History and literature; Church